2023
DOI: 10.1038/s41598-023-42139-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-dose ionizing radiation on genomic instability in interventional radiology workers

Dominika Kochanova,
Sachin Gulati,
Matus Durdik
et al.

Abstract: Interventional radiologists are chronically exposed to low-dose ionizing radiation (IR), which may represent a health risk. The aim of the present study was to evaluate genomic instability by analyzing chromosomal aberrations, micronuclei, and 53BP1 DNA repair foci in peripheral blood lymphocytes of radiologists. Based on the IAEA guidelines on biodosimetry using dicentrics, the average protracted whole-body dose in radiologists were estimated. Since preleukemic fusion genes (PFG) are the primary events leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, the results of a study on radiologists demonstrated that these individuals suffered from genomic instability, chromosomal aberrations, and genetic mutations in the DNA molecule in the long term (15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results of a study on radiologists demonstrated that these individuals suffered from genomic instability, chromosomal aberrations, and genetic mutations in the DNA molecule in the long term (15).…”
Section: Discussionmentioning
confidence: 99%
“…Image acquisition utilized a high-resolution monochrome megapixel charge-coupled device (CCD) camera with a resolution of 1280 × 1024 pixels. The microscope employed was connected to a motorized microscope Axioplan 2 Imaging E MOT [23,27].…”
Section: Automated High-throughput Scoring Of DC and Mnmentioning
confidence: 99%